Moringa oleifera leaf for replacing protein portion of soybean meal in the diet of young growing meat goats - J. Achmadi; E. Pangestu; S. Surahmanto; A. Muktiani; S. Sutrisno; M. Christiyanto; S. Surono; L. K. Nuswantara; A. Subrata (Diponegoro University, 2023)
In vitro ruminal feed fermentability test and feeding experiment were conducted to clarify the substitution of soybean meal with Moringa oleifera leaf powder (MOlp) in the diet of young growing goats. Five M. oleifera based feeds were studied in the test of in vitro ruminal fermentability: 0% MOlp, 25% MOlp, 50% MOlp, 75% MOlp and 100% MOlp. All feeds were designed to be isoprotein and isoenergy, containing 20% crude protein and 71 - 75% TDN. In the feeding experiment, three dietary experiments were offered to young growing Jawarandhu goats, aged 3 – 5 months with average body weight of 10 kg. The dietary experiments were 0% MOlp, 25% MOlp and 75% MOlp. All dietary experiments were designed to be isoprotein and isoenergy, containing 20% crude protein and 71 - 75% TDN. Result of the in vitro ruminal feed fermentability test showed that feed dry matter and crude protein digestibilities, ruminal concentrations of total VFA and NH3, and total ruminal protein production increased (p<0.05) in line with the level of MOlp in the experimental feeds. Result of feeding experiment revealed that nutrient intakes and body weight gain were not different (p>0.05) among treatment groups. Blood concentrations of protein, urea, ammonia, glucose, triglycerides, and cholesterol were similar in all groups. The dietary treatment did not effect significantly (p>0.05) on some hematological parameters. M. oleifera leaf could replace protein portion of soybean meal in the diet of young growing meat goats without negative effect on productive performances.